Study on the presence of the theme "autism spectrum disorder (ASD)" in undergraduate pedagogy curricula (Olhar de Professor, 2021)
This paper presents the results of a research that aimed to identify the presence of the theme of autism spectrum disorder (ASD) in the programmatic contents of the undergraduate disciplines of pedagogy courses to extract, through content analysis (BARDIN, 1977), the various understandings concerning the theme in these curricula. To this end, we studied the menus of the disciplines of undergraduate curricula in pedagogy of three Higher Education Institutions in the city of São Paulo. From the analysis procedure, three categories were formulated: legislative aspects of the ASD; medical-psychological aspects of ASD and subjective aspects of ASD. It was possible to apprehend the prevalence of legislative aspects – which refers to the presence of legislation and normative documents – and medical-psychological - a category in which the definition of diagnosis and human development are prevalent - in the approach to the theme proposed by the disciplines.
Keywords: Inclusive Education; Autism Spectrum Disorder; Pedagogy